Implementasi Float Switch Level Sensor, Ultrasonik Sensor, dan Water Flow Sensor pada Prototipe Sistem Kendali Pompa Asam Sulfat Berbasis Arduino - Muhammad Adit Dwiky; Atmiasri Atmiasri (Pusat Riset dan Inovasi Nasional, 2025)
The handling of hazardous chemicals, such as sulfuric acid (H₂SO₄), in industrial processes requires a control system that ensures both operational reliability and safety. Manual pump operation in such contexts carries a significant risk of over-pumping, leaks, and exposure, which can lead to environmental contamination and safety hazards. To address this issue, this study focuses on the design and implementation of an automatic pump control system prototype using the Arduino Mega 2560 microcontroller. The system integrates three key sensors: a float switch for basic level detection, an ultrasonic sensor (HC-SR04) for precise liquid level measurement, and a water flow sensor (YF-S201) for monitoring flow rate. The prototype is programmed to automatically regulate pump operation based on real-time input from the sensors. When the liquid level reaches a predetermined threshold, the pump activates or deactivates accordingly. Sensor data, including fluid height and flow rate, are displayed in real-time on a 3.5-inch TFT LCD, allowing for direct operator monitoring. Both the hardware configuration and software algorithms were tested for functionality, response time, and accuracy under simulated industrial conditions. The results indicate that the system can reliably control pump activation with minimal error rates. The ultrasonic sensor demonstrated an average measurement error of 0.94%, while the water flow sensor achieved an error rate of 1.19%. The software successfully processed sensor data and executed output actions consistent with the programmed logic. Overall, this automated control system proved effective in mitigating the risk of over-pumping and improving safety in handling hazardous chemical fluids. Given its accuracy, reliability, and cost-effectiveness, the developed prototype is considered suitable for small- to medium-scale industrial applications, with potential for further refinement to meet larger operational demands.